Michal the Misinterpreted - White, Ellen (Journal for the study of the Old Testament, 2007)
Interpretation is always done within one’s own context. It is impossible to interpret a text without the impact of one’s worldview and ideological positions seeping into the interpretive process. Due to this contextual approach to interpretation, one must analyze the history of interpretation from a critical viewpoint, rather than blindly accepting a historical understanding. The character of Michal in the books of Samuel is a good example of how the history of interpretation can be guided by the interpreter’s ideology and also why the historical understandings need to be re-evaluated. This article contains one example of how such interpretations can be challenged and reassigned in relation to Michal.